2017
DOI: 10.1080/24750573.2017.1380920
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between psychopathology and cognitive functions with cytokines in clinically stable patients with schizophrenia

Abstract: OBJECTIVES: Inflammation and the cytokine hypotheses have been proposed for schizophrenia. Several proinflammatory and anti-inflammatory cytokines have been studied in drug-naive, first-episode, and/or chronic schizophrenia patients. However, there were limited data on clinical stable outpatients reflecting daily routine. The aim of this study was to compare the serum levels of cytokines, including transforming growth factor-beta (TGF-β), interleukin-6 (IL-6), and tumour necrosis factor-alpha (TNF-α), between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The predicted TGFB1-Mental Disorders link, which later were published in López-González et al (2019 ), supports the theory that dysfunction of the immune system plays an important role in the etiology of mental illnesses, such as schizophrenia and depression ( Frydecka et al, 2013 ; Bialek et al, 2020 ). In fact, significantly higher serum levels of the IL-6 and TGFB1 cytokines have been reported in patients with schizophrenia compared to healthy controls ( Ergün et al, 2017 ) and mutations in TGFB1 have been associated with the susceptibility and treatment response of schizophrenia ( Frydecka et al, 2013 ) and major depressive disorder ( Bialek et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The predicted TGFB1-Mental Disorders link, which later were published in López-González et al (2019 ), supports the theory that dysfunction of the immune system plays an important role in the etiology of mental illnesses, such as schizophrenia and depression ( Frydecka et al, 2013 ; Bialek et al, 2020 ). In fact, significantly higher serum levels of the IL-6 and TGFB1 cytokines have been reported in patients with schizophrenia compared to healthy controls ( Ergün et al, 2017 ) and mutations in TGFB1 have been associated with the susceptibility and treatment response of schizophrenia ( Frydecka et al, 2013 ) and major depressive disorder ( Bialek et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 showed that in the schizophrenia group, statistically, there was no significant correlation between TNF-alpha level and PANSS score (p = 0.594), the correlation was very weak, but it had a positive correlation means that the higher TNF-alpha level was, the higher PANSS score would be. Ergün et al also reported the lack of correlation between TNF-alpha and PANSS score, [13], with a negative correlation direction. Kubistova et al [14], Ajami et al [15], and Luo et al [16] reported similar results, who found that there was no TNF-alpha correlation with PANSS score on PwS.…”
Section: Correlation Of Tnf-alpha Level With Panss Scores In the Schizophrenia Groupmentioning
confidence: 98%
“…In patients with schizophrenia, elevated cytokine levels such as TNF-α, transform beta growth factor, IL-6, IL-1β receptor, IL-1 blocker, IL-2 receptor, and IL-12 receptor have been identified; however, numerous studies have also found some controversial results. These variations relate to the determination of exclusion criteria, nature of the study, sample size, patient clinical status, metabolic and/or inflammatory disorder comorbidity, body mass index (BMI) potential effects, and smoking status may all cause differences in this variation [10].…”
Section: Introductionmentioning
confidence: 99%